Thermal energy storage design for emergency cooling - Basgall, Lance Edgar (Kansas State University, 2010)
Emergency cooling systems are applied to any application where the loss of cooling results in damage to the product, loss of data, or equipment failure. Facilities using chilled water for cooling that experience an electrical power outage, even a small one, would cause the chiller to shut down for 20 minutes or more. If emergency cooling is not available, temperatures would continue to increase to dangerous levels, potentially damaging the facility. Examples of facilities that could be protected by having emergency cooling systems are data centers, hospitals, banks, control rooms, laboratories, clean rooms, and emergency shelters among others. This project addresses the current lack of information and methods needed to correctly design emergency cooling systems. Three application uses were investigated for the possible benefits of having emergency cooling systems. The software TRNSYS was used to simulate five typical emergency cooling systems for each of the three applications. The characteristics and differences of the systems developed from the simulations were then analyzed and documented. The five systems simulated include a pressurized chilled water tank (parallel), atmospheric chilled water tank (parallel and series), low temperature chilled water tank (parallel), and ice storage tank (series). Simulations showed that low temperature chilled water tanks were less stratified than regular chilled water tanks by approximately 10%. Simulations also showed that the differences between atmospheric and pressurized tanks were negligible. Each tank discharged energy in the same manner and managed to replenish itself in the same amount of time. Examination of the different system configurations showed that tanks in series with the thermal load have issues with recharging due to its inability to isolate itself from the thermal load. It was also observed that while low temperature chilled water and ice storage tanks had the potential of reducing the storage tank volume, the amount of time ragged cooling will last is decreased by at least a factor of two. The examination of the five systems produced the desired design methodologies needed to address the lack of information on emergency cooling systems. With the reported information designers can effectively engineer systems to meet their needs.
Keywords: Thermal energy storage; Chilled water; Ice storage; Emergency cooling; Engineering, General (0537); Engineering, Mechanical (0548)